PROFIL KOMPOSISI DAN SIFAT FUNGSIONAL SERAT PANGAN DARI AMPAS EXTRAKSI PATI BEBERAPA JENIS UMBI - Nurdjanah, Siti; Elfira, Winny (Jurnal Teknologi & Industri Hasil Pertanian, 2009)
Indogeneous tubers such as cassava, arrow root dan  colocasia yam  are widely grown in the tropics.  Some of the tubers are waste of starch raw material, which leaves some starch residue.  To date, although this residue contains appreciable amount of dietary fiber, research on this area has not been intensely investigated. The aims of this research were to investigate the composition and the functional properties of dietary from cassava, arrow root and colocasia yam.  The results showed that starch residue from cassava, arrow root and colocasia yam contains dietary fiber components such as pectin, hemicellulose, and cellulose around 5-12%, 9-12%, 6-19% respectively.  The hemicellulose of the starch residues has water uptake and oil uptake around 30-40% and 14-23%.  The results show that the starch residue from cassava, arrow root and colocasia yam have the potential to be developed as dietary fiber. Keywords: arrow root, cassava, colocasia, dietary fiber